PENGARUH PROSES PEMASAKAN TERHADAP PERUBAHAN KANDUNGAN PROTEIN DAN ASAM AMINO IKAN SEMBILANG (Paraplotosus Albilabris) - vivi_warningsih vivi_warningsih; mery_sukmiwaty mery_sukmiwaty; sumarto_sumarto sumarto_sumarto (Fakultas Perikanan dan Kelautan, Universitas Riau, 2018)
This researh was aimed to determine the changes of protein and amino acid profil content of catfish (Paraplotosus albilabris). The research method is conducted by experimental method that was doing a series of experimental research of different cooking process in catfish. The design used was a completely randomized design non factorial with 4 levels treatment namely:without cooking process as a control (P0), boiling cooking process (P1), boiling cooking process with salt (P2), and steaming cooking process (P3). The results showed that the nutritional content of catfish after the different cooking treatment gave a real effect on the water, ash, fat, and protein content and gave different amino acid profile each different cooking process. Boiling cooking process had amino acid content 90.58% and closed to amino acid content of fresh catfish (control). The binding capacity of catfish flour from different raw material gave the different of water holding capacity value ie catfish flour from fresh condition 3.3g/g (P0), boiling cooking process 3.1g/g(P1), boiling cooking process with salt 3.1g/g(P2), and steaming cooking process 3.7 g/g (P3).